Transformative Dialogic Literature Teaching fosters adolescents' insight into human nature and motivation. (October 2019) - Schrijvers, Marloes; Janssen, Tanja; Fialho, Olivia; De Maeyer, Sven; Rijlaarsdam, Gert
Abstract: This quasi-experimental study assessed the effects of the newly developed Transformative Dialogic Literature Teaching (TDLT) intervention on 15-year-old students' insight into human nature, eudaimonic reasons for reading, use of reading strategies, and motivation for literature education. Six TDLT units centered around short stories about "justice and injustice". Students were stimulated to engage in internal dialogues with stories and in external dialogues with peers about stories and reading experiences. TDLT students (n = 166) were compared to students who received regular literature teaching (RLT) focused on analysis of literary texts (n = 166). Analysis of quantitative and qualitative data indicated that TDLT fostered students' insight into human nature, eudaimonic reasons for reading, reported use of strategies to deal with difficulties in literary texts, and motivation for literature education, whereas RLT did not. Strategy use and one motivational factor mediated effects of TDLT to a small extent. Limitations and implications are discussed. Highlights: Literary instruction may foster novice readers' insight into human nature. Transformative Dialogic Literature Teaching fostered this insight in adolescents. The reader-oriented TDLT approach was more effective than an analytical approach. TDLT also enhanced use of literary reading strategies and motivation. Strategy use and motivational factors played small mediating roles.